Student Collaboration Skills through the Implementation of the Project Based Learning (PjBL) Model on Blood Circulatory System Material - Yulisma, Lia -; Hendrawati, Mitha Aprilia; Ernasari, Euis (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
Education in the 21st century has the challenge of preparing human resources that are able to compete in the era of globalization, so it is important to master 4C learning skills, one of which is collaboration skills. The PjBL model is related to collaboration skills because throughout the learning implementation process, students generally have the potential to increase self-involvement. This research aims to analyze the provision of students' collaboration skills through the application of a project based learning model on circulatory system material. In this research, the method used was a descriptive method with a sample of 36 students. The sample was obtained using a purposive sampling technique. Data was collected through instruments in the form of observation sheets. Research data was analyzed to get an overview of students' collaboration skills and a description of each group for each indicator. Based on the findings obtained, the overall average results of student collaboration skills are included in the very high category. Based on this, it can be concluded that the application of the project based learning model to the circulatory system material has been proven to be able to provide students with effective collaboration skills. Keywords: bloodstream system; collaboration skills; project-based learning